Application Development by Reusing Object-Oriented Frameworks - Lopes, S.F.; Tavares, A.C.; Silva, C.A.; Monteiro, J.L. (EUROCON 2005 - The International Conference on Computer as a Tool, 2005)
Object-oriented frameworks are an important form of reuse that can help to decrease significantly the application development time and cost. Although widely known, there are still some difficulties associated with them that are critical to its success. These problems have to be alleviated to make the framework reuse an attractive alternative to application development. We focus on the issues regarding the framework reuse process, more specifically, framework architecture description, its adaptation with application specific components, and final application instantiation. This paper discusses our position on these subjects and, based on previous work, we propose a different approach and appropriate tool support